Arc Interacts with the Integral Endoplasmic Reticulum Protein, Calnexin - Myrum, Craig; Soulé, Jonathan; Bittins, Margarethe; Cavagnini, Kyle; Goff, Kevin; Ziemek, Silje K.; Eriksen, Maria S.; Patil, Sudarshan; Szum, Adrian; Nair, Rajeevkumar R.; Bramham, Clive R. (Frontiers in Cellular Neuroscience, 2017)
Activity-regulated cytoskeleton-associated protein, Arc, is a major regulator of long-term synaptic plasticity and memory formation. Here we reveal a novel interaction partner of Arc, a resident endoplasmic reticulum transmembrane protein, calnexin. We show interaction between recombinantly-expressed GST-tagged Arc and endogenous calnexin in HEK293, SH-SY5Y neuroblastoma, and PC12 cells. The interaction was dependent on the central linker region of the Arc protein that is also required for endocytosis of AMPA-type glutamate receptors. High-resolution proximity-ligation assays demonstrate molecular proximity of endogenous Arc with the cytosolic C-terminus, but not the luminal N-terminus of calnexin. In hippocampal neuronal cultures treated with brain-derived neurotrophic factor, Arc interacted with calnexin in the perinuclear cytoplasm and dendritic shaft. Arc also interacted with C-terminal calnexin in the adult rat dentate gyrus. After induction of long-term potentiation in the perforant path projection to the dentate gyrus of adult anesthetized rats, enhanced interaction between Arc and calnexin was obtained in the dentate granule cell layer. Although Arc and calnexin are both implicated in regulation of receptor endocytosis, no modulation of endocytosis was detected in transferrin uptake assays. Previous work showed that Arc interacts with multiple protein partners to regulate synaptic transmission and nuclear signaling. The identification of calnexin as a binding partner further supports the role of Arc as a hub protein and extends the range of Arc function to the endoplasmic reticulum, though the function of the Arc/calnexin interaction remains to be defined.